Help for the Workers of Spain Fund (draft circular) - Tewson, Vincent (1937)
028-0044-001 NATIONAL COUNCIL OF LABOUR. TRANSPORT HOUSE, SMITH SQUARE, LONDON, S.W.1 TRADES UNION CONGRESS Secretary: Walter M. Citrine (Victoria 9830) THE LABOUR PARTY Secretary: J. S. Middleton (Victoria 8016) PARLIAMENTARY LABOUR PARTY Secretary: H. Scott Lindsay (Whitehall 6240) Our Ref: HVT/MS/120 Dear Sir (Madam), HELP FOR THE WORKERS OF SPAIN FUND. The National Council of Labour send [wish to convey] to you their very best thanks for your gift [the contribution you have sent] to the above Fund. We can assure you that it is very much appreciated and will be used to the best possible advantage. Enclosed herewith is our official receipt for the amount sent. Yours sincerely, Joint Secretary. H.V. Tewson Joint Secretary. ENC: Receipt. 292/946/28/44